Sintesis Komposit ZnO/Ca3(PO4)2 menggunakan metode Sol-gel sebagai Material Fotokatalis Limbah Cair Industri (Metilen Biru) - Nurul Fajri R Tang; Dahlang Tahir; Heryanto Heryanto (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2022)
This study use composite ZnO/Ca3(PO4)2 material was synthesized by using the sol-gel method. Composite material ZnO/Ca3(PO4)2 is made from beef tailbone which is heated at a temperature of 300  for 10, 90, 120, and 240 minutes. Samples were characterized using X-ray diffraction ( XRD ), Fourier transforms infrared ( FTIR ) dan UV - Visible ( UV-Vis ). Quantitative analysis of XRD spectra showed the lowest crystal size with a diameter of 21.71 nm on heating for 90 m. The results of the FTIR spectrum show the vibration of the PO4 and ZnO bond at wavenumber 1039 cm-1 and 400-500 cm-1. The best percentage of degradation is indicated by small crystal size and high infrared absorption by O-H bonds. The degradation results reached 93.98% in just 5 minutes with an energy gap of 3.84 eV. Based on these results, the ZnO/Ca3(PO4)2 composite is one of the promising and potential catalyst materials to solve the problem of industrial waste pollution, especially methylene blue.